The Paradox of Indonesia Cyberspace Policy and Cooperation: Neoclassical Realism Perspective - Muhammad Abdurrohim; Indah Kumalasari; Fathur Rosy (Jurnal Hubungan Internasional, 2023)
Cyberspace is a new threat to state security, especially in Indonesia. The increase of internet users in Indonesia is followed by several policies Jakarta takes to adapt to the fast pace of cyberspace challenges. To manage cyberspace in Indonesia, the government has developed ITE Law to regulate Indonesia’s cyberspace and prevent threats coming from within. Moreover, realizing cyberspace offers many opportunities. The government also cooperates with other actors like ASEAN to formulate ASEAN Digital Masterplan to enhance cyberspace contribution toward economic recovery after the COVID-19 pandemic. However, there is a contradiction between ITE Law, especially the Regulation of the Minister of Communication and Informatics No. 5 of 2020, and the cyberspace cooperation that the government tries to impose. These phenomena raise the question of why the Indonesian government takes contradiction policy on cyberspace between domestic and international levels. This research examined the reason behind the paradoxical policy of the Indonesian government’s ITE Law and the ASEAN Digital Masterplan regarding cyberspace policy, especially from 2016 to 2021. A qualitative method was employed to achieve the objective, with disciplined configurative reports and government documents regarding its cyber policy as the data. The data were analyzed using the theory of neoclassical realism to identify the Indonesian government’s cyberspace policy behavior on domestic and international levels. This paradoxical situation between the domestic and international levels of the Indonesian government’s cyberspace policy was created by how the Indonesian government identified threats. The Indonesian government still faced instability at the domestic level to identify the category of threats toward the regime due to the inheritance of the authoritarian regime government model it experienced before. The opposite response at the international level occurred because the socialization and institutionalization in the region have created strategic culture. Accordingly, the strategic culture of cyberspace has restricted the Indonesian government from applying the same idea at the domestic level. The Indonesian government should adapt the popular strategic culture at the international level to ensure prestige.